The Role of Reflective Thinking in Enhancing Mathematical Problem-Solving Skills - Valeria Zebua; Netti Kariani Mendrofa; Ratna Natalia Mendrofa; Sadiana Lase (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study was motivated by preliminary findings suggesting that students' mathematical problem-solving skills were deficient. Students encountered challenges in comprehending problem material, formulating solution strategies, executing problem-solving procedures, and evaluating their responses. This study sought to elucidate the function of reflective thinking in enhancing students' mathematical problem-solving capabilities concerning matrices. A descriptive qualitative methodology was utilised, employing 22 eleventh-grade students as participants in the research. Data were gathered by observation, assessments, interviews, and documentation, and were analysed through data reduction, data presentation, and conclusion formulation. The results indicated disparities in students' mathematical problem-solving proficiency across four tiers: extremely high (3 students; mean score = 85.4), high (4 students; mean score = 68.2), moderate (7 students; mean score = 51.7), and low (8 students; mean score = 29.9). This study was prompted by initial observations suggesting that students' mathematical problem-solving skills were deficient. Students encountered challenges in comprehending problem material, formulating solution strategies, executing problem-solving procedures, and evaluating their responses. This study sought to elucidate the function of reflective thinking in enhancing students' mathematical problem-solving skills concerning matrices. A descriptive qualitative methodology was utilised, employing 22 eleventh-grade students as participants in the research. Data were gathered by observation, assessments, interviews, and documentation, then analysed through data reduction, data presentation, and conclusion formulation. The results indicated discrepancies in students' mathematical problem-solving capabilities across four tiers: very high (3 students; mean score = 85.4), high (4 students; mean score = 68.2), moderate (7 students; mean score = 51.7), and low (8 students; mean score = 29.9). Students possessing advanced reflective thinking skills demonstrated a profound understanding of problems, the capacity to identify suitable techniques, rectify errors, and articulate their thought processes eloquently and logically. The findings suggest that reflective thinking significantly enhances pupils' mathematical problem-solving skills. As students' reflective thinking skill increases, their capacity to comprehend challenges, devise and execute suitable techniques, and independently, critically, and systematically assess and enhance their solutions improves.